Effectiveness of CO2 Capture by Arthrospira platensis Microalgae from a Mixture Simulating Flue Gases - Vlaskin M.S. (2023)
© 2023, Pleiades Publishing, Inc.Abstract: Decarbonization of the power industry requires the search of methods for cutting down the greenhouse gas emissions into the environment, including utilization of carbon dioxide generated during combustion of hydrocarbon fuels at power facilities. One of the promising methods is the capture of carbon dioxide by biota, not only by terrestrial plants but also by aquatic organisms, including specially cultivated microalgae. In this work, the efficiency of the capture of carbon dioxide with a concentration of approximately 6% from a gas–air mixture by Arthrospira platensis (Nordst.) Geitl microalgae was studied. This concentration has been selected on the basis of experimentally determining the CO2 content in flue gases formed at industrial gas-piston power plants. The experiments were performed using a closed photobioreactor with a capacity of 100 dm3 installed in a gas chamber enabling elevated СО2 concentrations in an air–gas environment to be created. The maximum growth rate of the microalgae biomass is 0.140 g/(dm3 day). The effectiveness of CO2 capture by microalgae was 0.220 g/(dm3 day) based on the results of determination of the microalgae productivity by biomass and 0.235 g/(dm3 day) based on the results of direct measurement of СО2 concentration in the chamber. The concentration of the main nutrients (such as bicarbonates, phosphates, and nitrates) in the medium decreased by 25–50% during the experiment period. A comparative analysis of the consumption of carbon-containing components of the medium (Formula presented.) by microalgae during the bubbling of cultural liquids with a gas–air mixture with different carbon dioxide content was performed. In general, good viability of A. platensis microalgae (high quality of biomass and high rate of its growth) was demonstrated when it was cultivated in an atmosphere with a high concentration (6%) of CO2.